Numerical study of laminar non-premixed biogas-air flames behind backward facing steps - Alagani Harish; Vasudevan Raghavan (Archive of Mechanical Engineering, 2022)
Biogas, a renewable fuel, has low operational stability range in burners due to its inherent carbon-dioxide content. In cross-flow configuration, biogas is injected from a horizontal injector and air is supplied in an orthogonal direction to the fuel flow. To increase the stable operating regime, backward facing steps are used. Systematic numerical simulations of these flames are reported here. The comprehensive numerical model incorporates a chemical kinetic mechanism having 25 species and 121 elementary reactions, multicomponent diffusion, variable thermo-physical properties, and optically thin approximation based volumetric radiation model. The model is able to predict different stable flame types formed behind the step under different air and fuel flow rates, comparable to experimental predictions. Predicted flow, species, and temperature fields in the flames within the stable operating regime, revealing their anchoring positions relative to the rear face of the backward facing step, which are difficult to be measured experimentally, have been presented in detail. Resultant flow field behind a backward facing step under chemically reactive condition is compared against the flow fields under isothermal and non-reactive conditions to reveal the significant change the chemical reaction produces. Effects of step height and step location relative to the fuel injector are also presented.